Regulatory quality in Europe : Concepts, measures and policy processes - Radaelli, Claudio M. (Book collections on Project MUSE., 2007)
The European Union and its member states are investing in ambitious programmes for?better regulation? and targets of regulatory quality. This book lifts the veil of excessively optimistic propositions covering the whole better regulation agenda. It provides an innovative conceptual framework to handle the political complexity of regulatory governance. It approaches better regulation as an emerging public policy, with its own political context, actors, problems, rules of interaction, instruments, activities and impacts. Focusing on the key tools of impact assessment, consultation, simplificati.